How strain and production system effects chicken welfare and quality in meat - Wilhelmsson, Sofia (2014)
There are several reasons why organic chicken production is scarce in Sweden. Lack of slow growing (SG) strains combined with higher production costs, lower meat-yield and uncertainty of consumers’ willingness to pay seems to be the main reasons. EU-legislations imply use of indigenous slow- or medium growing strains in organic production, nevertheless, fast growing (FG) broilers are often used due to their effectiveness. Increased consumption of processed food creates a market for conventionally rearing of very heavy broilers. Through selection programs FG broilers gain weight fast leading to inactivity, imbalanced bodies, disease and high mortality rates. This combined with legislations by KRAV regarding daily growth and slaughter age make FG broilers used in organic production questionable. SG strains adapt well and benefit from extensive conditions and increased motion whilst FG broilers cannot fully use outdoor areas. In organic production, FG broilers have significantly higher mortality rates than medium and SG chickens. Quality of chicken meat is mainly afflicted by genotype, maturity, sex and production system. Related to age, meat from SG strains contains more protein and half as much intramuscular fat than meat from FG broilers. For several years, FG broiler meat qualities have been based on offering consumers’ cheap meat. Consumers’ today are more concerned about animal-welfare than in the past and the market for extensive produced poultry are growing.